Dari Manna ke Meja Persekutuan: Membaca Matius 6:11 sebagai Dasar Teologis Solidaritas Pangan Gereja di Indonesia - Iwan Sembiring; Yohanes Parapat (JURNAL LUXNOS, 2026)
This article examines the petition “Give us this day our daily bread” in Matthew 6:11 as the theological basis for the church's food solidarity. Matthew 6:11 is often read primarily as a personal prayer for the fulfillment of daily needs. This article offers an exegetical-theological reading that emphasizes that this petition not only shapes a spirituality of sufficiency but also builds a communal imagination of food as a gift from God to be received, managed, and shared. Using intertextual exegesis, this article interprets Matthew 6:11 in dialogue with the pedagogy of manna in Exodus 16, the prayer of Agur in Proverbs 30:8, and the spirituality of sufficiency in Philippians 4:12. The study reveals that “today's bread” encompasses three main dimensions: daily dependence on God, restrictions on an accumulation mentality, and a call to build a just table of fellowship. This article then contextualizes these exegetical findings within the global and Indonesian food crises and proposes church food solidarity as a diaconal practice rooted in prayer, exegesis, and the communal life of God's people.